A Clinical Validation of Self‐Reported Periodontitis Among Participants in the Black Women's Health Study. Issue 6 (1st June 2017) - Heaton, Brenda; Gordon, Nicholas B.; Garcia, Raul I.; Rosenberg, Lynn; Rich, Sharron; Fox, Matthew P.; Cozier, Yvette C.
Abstract : Background: There is a paucity of data on the validity of self‐report of periodontal disease in African Americans. The Black Women's Health Study (BWHS), a United States national cohort study of 59, 000 black women followed via mailed questionnaires since 1995, offered the opportunity to clinically validate self‐reported periodontitis among a sample of participants. Methods: Oral health questionnaires were sent to study participants residing in Massachusetts. Respondents living in the Boston metro area were invited for clinical examination. Self‐reports were compared with clinical data obtained from the 77 women (mean age: 59 years) who were examined. The authors examined the predictive ability of individual and combined questionnaire items with respect to clinical periodontal disease severity. Validation parameters were calculated for each question, and receiver operating characteristic statistics were generated to compare questionnaire items. Results: Periodontitis prevalence in the validation sample was 24% for severe periodontitis and 61% for moderate disease. Performance of individual questionnaire items with respect to predicting periodontitis was better for severe compared with moderate disease. Combinations of questionnaire items improved the predictive ability with respect to severe disease beyond that of individual questionnaire items. Conclusions: Prevalence of severe periodontitis was similar to other age‐comparable populations, without regard for race or sex, whereas prevalence of total periodontitis (moderate and severe) among women of similar age and/or race was much higher. Predictive ability of questionnaire items assessed in the BWHS was similar to that in other studies.